2017
DOI: 10.18632/oncotarget.15483
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin abrogates renal interstitial fibrosis by regulating macrophage polarization via inhibition of Toll-like receptor 4 signaling

Abstract: Renal fibrosis is a common feature of chronic kidney disease (CKD). To inhibit the CKD process, it is important to prevent renal fibrosis, though CKD remains incurable. Renal fibrosis can be inhibited by relaxin in several experimental models, but the mechanism of relaxin for antifibrotic potential is still not clear. And here we have studied the role of relaxin in macrophage polarization and renal inflammation after unilateral ureteral obstruction (UUO). Our results show that relaxin can downregulate the Toll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Previous studies have implicated IL-33/ST2 axis in downregulation of TLR signaling [ 29 ]. The activation of TLR signaling can shift macrophage polarization toward the M1 phenotype [ 30 ]. But if TLR signaling is involved in IL-33/ST2 axis-mediated macrophage polarization, regulation is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated IL-33/ST2 axis in downregulation of TLR signaling [ 29 ]. The activation of TLR signaling can shift macrophage polarization toward the M1 phenotype [ 30 ]. But if TLR signaling is involved in IL-33/ST2 axis-mediated macrophage polarization, regulation is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant H2 relaxin was generously provided by Corthera Inc (San Carlos, CA, USA; a subsidiary of Novartis AG, Basel, Switzerland) and is bioactive in rats 21,22,24,25,[38][39][40] and mice 15,19,25,39,41,42 . A rat and mouse model of UUO, which mimics the pathology of human progressive renal disease 43,44 , was used as an experimental model of primary tubulointerstitial fibrosis.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15] Additionally, RLX can inhibit inflammatory cell influx post-injury [16][17][18] and influence macrophage polarization towards a M2 pro-repair macrophage phenotype. 19 Signal transduction studies have shown that activation of RXFP1 on renal and cardiac myofibroblasts by RLX directly increases cGMP 20 or signals through an ERK1/2 phosphorylation and neuronal nitric oxide (NO) synthase (nNOS)-NO-sGC-cGMP-dependent pathway to inhibit TGF-1 signal transduction at the level of intracellular Smad2 phosphorylation (phospho-Smad2). 13,[21][22][23] This in turn disrupts the pro-fibrotic actions of TGF-1 on myofibroblast differentiation and aberrant ECM deposition.…”
mentioning
confidence: 99%
“…Furthermore, relaxin decreases granule exocytosis and mast cell degranulation to reduce proinflammatory and allergic cytokines such as histamine, leukotrienes and serotonin . Relaxin can also inhibit the endothelial adhesiveness to neutrophils and the infiltration of macrophages which are crucial for the recruitment and migration of inflammatory cells to the site of injury (Hewitson et al, 2007;Martin et al, 2018;Nistri et al, 2003), inhibit toll-like receptor-4 signaling, and promote tissue-repairing M2 macrophage polarization (Chen et al, 2017). Moreover, relaxin inhibits NLRP3 inflammasome activity, which is known to increase interleukin (IL)-1β activity (Raleigh et al, 2017), and also plays a role in inhibiting NFkB signaling, a crucial transcription factor that regulates many inflammatory genes (Martin et al, 2018).…”
Section: Relaxin Effects On Inflammation and Fibrogenesismentioning
confidence: 99%